2018
DOI: 10.1016/j.psychres.2018.05.085
|View full text |Cite
|
Sign up to set email alerts
|

Childhood malnutrition and maltreatment are linked with personality disorder symptoms in adulthood: Results from a Barbados lifespan cohort

Abstract: Both childhood malnutrition and maltreatment are associated with mental health problems that can persist into adulthood. Previously we reported that in Barbados, those with a history of infant malnutrition were more likely to report having experienced childhood maltreatment. Few studies, however, address the long-term outcomes of those who have been exposed to both. We assessed the unique and combined associations of a history of early malnutrition and childhood maltreatment with personality pathology in mid-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 62 publications
(85 reference statements)
4
24
0
Order By: Relevance
“…First, we found that childhood maltreatment experiences had a direct effect on adolescent personality functioning. This finding is consistent with a large body of research conducted in adult samples that found a link between childhood maltreatment and an increased risk for maladaptive personality traits and personality pathology (Hengartner et al, 2015;Hock et al, 2018). In particular, traumatic childhood experiences are considered a significant predictor for borderline personality features in adolescents and adults (Baryshnikov et al, 2017;Lobbestael, Arntz, & Bernstein, 2010;Mosquera, Gonzalez, & Leeds, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…First, we found that childhood maltreatment experiences had a direct effect on adolescent personality functioning. This finding is consistent with a large body of research conducted in adult samples that found a link between childhood maltreatment and an increased risk for maladaptive personality traits and personality pathology (Hengartner et al, 2015;Hock et al, 2018). In particular, traumatic childhood experiences are considered a significant predictor for borderline personality features in adolescents and adults (Baryshnikov et al, 2017;Lobbestael, Arntz, & Bernstein, 2010;Mosquera, Gonzalez, & Leeds, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, infants and children exposed earlier and more sustainably to poor states of nutrition have a greater probability of experiencing more severe and chronic health outcomes as a result. In utero as well as cohort studies of the Latin Americas and the Caribbean and European societies suggest that foetus exposed to poor maternal nutrition, and children 0-6 months old exposed to poor nutritional profiles are more likely to be hospitalised, exhibit mental disorders such as personality and schizoid disorders and have chronic diseases including hypertension and diabetes [22,23]. Moreover, European evidence points to greater episodes of diarrhoea, vomiting, poor recovery, longer hospital stays and greater health care costs in admitted children with body mass indices less than two standard deviations in children compared to healthy controls [24].…”
Section: Malnutrition Across the Lifespanmentioning
confidence: 99%
“…Nevertheless, the morbidity associated with nutritional inadequacies in children can be attenuated with early and appropriate nutritional interventions. Studies concerning the Caribbean and West African population have shown that the rate of hospitalisation and mental illness associated with poor childhood nutrition declined with nutritional supplementation in both Barbados and Mauritius [23].…”
Section: Malnutrition Across the Lifespanmentioning
confidence: 99%
“…The following two hypotheses and one research question were formulated. First, following others, 17,19 we expected that childhood trauma would be more often reported by male incarcerated people with BPD, compared to normative data. 25 Second, following others, 19,22,23 we expected an association between levels of dissociation and the prevalence rates of self-reported childhood and current/adulthood trauma.…”
Section: Introductionmentioning
confidence: 95%